Examining the link between information and communication technologies and the UN Sustainable Development Goals. (1st March 2021) - Adam, Ibrahim Osman; Dzang Alhassan, Muftawu
This study examines the empirical link between information and communication technologies (ICTs) and the Sustainable Development Goals (SDGs) in 143 countries for 2016. The adoption of the 2030 agenda of the SDGs has prompted the creation of research streams across disciplines, including the information systems discipline. Despite these, extant literature since the adoption of the SDGs has sought to highlight the importance of ICTs in achieving the 2030 milestones. Whilst many of these studies proffer the ICT‐SDG linkage, there is no empirical evidence that examines this linkage. This study draws on archival data and structural equation modelling to empirically show the relationship between ICTs and the SDGs, on one hand, and the mediating role of human development, on the other. Our findings show that there is a direct significant relationship between ICTs and the SDGs and that investment in ICTs will significantly accelerate the achievement of the 2030 targets of the SDGs. Further, human development plays a significant mediating role in this relationship. The policy implications are discussed.